Peran Pelatih dalam Membentuk Semangat Juang Atlet Muda di Klub Sepak Bola - Hidayat, Muhammad; Saleh, Andi Muh.; Harpawansyah, Harpawansyah; Idzan, Ferry; Fadli, Muhammad; Rango, Apriani; Amin, Nursalehuddin N; Effendy, Titin Valentyn; Mus, Muhammad Taufiq Ismail; Jufri, Muhammad Chaidir Jufri10 Chaidir (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2022)
This study aims to explore the role of coaches in developing the fighting spirit of young athletes in soccer clubs. Fighting spirit is a fundamental psychological aspect that determines an athlete's success in competition, but its development is often overlooked in the training process. The study used a qualitative approach with a case study design at three soccer clubs in West Java. Data were collected through in-depth interviews with coaches and young athletes (aged 14-18), participant observation during training and matches, and analysis of training program documents. The results revealed that the coach's role in developing the fighting spirit of athletes is complex and multidimensional, encompassing functions as an effective communicator, a creator of a conducive training environment, an individual motivator, a role model, and a manager of realistic expectations. Successful coaches are those who are able to create positive interpersonal relationships, provide constructive feedback, consistently apply standards, and understand the psychological characteristics of young athletes. The findings also demonstrate the importance of balancing challenge and support in developing athletes' mental resilience. This study provides a theoretical contribution to understanding the psychological dimensions of coaching and practical applications for developing holistic athlete training programs. Recommendations include improving coaches' competency in sport psychology, developing a comprehensive evaluation system, and longitudinal research to understand the long-term impact of coaching on career athletes.